BEBERAPA HAL YANG PERLU DIPERHATIKAN DALAM MELAKUKAN ANALISIS SISTEM AGROINDUSTRI TERPADU - Soekartawi Soekartawi (Departemen Agribisnis, FEM-IPB, 2007)
The term of agro-industry has widely used as an umbrella to describe the business of food producers, processors, sellers, and services. Briefly, the definitions of agro-industry can be grouped into two different approaches. The first is an industry using agricultural products as its main input material, thus, agro-industrial studies emphasize the food processing management within agro-based enterprises that process mainly agricultural products. The second relates to a development stage, placing agro-industry between agricultural and industrial development where it is often used for sustainable agricultural development, sustainable agro-industrial development, and sustainable development.In order to gain maximum outcome effectively and efficiently, the implementation of the above concepts is named ‘Integrated Agro-industry System’ (IAS), i.e. the integration of the function and role of agro-industry components for making better outcome in the relatively long period. IAS is expected to contribute more significantly in (a) enhancing income and profitability for producers or processors and ultimately increasing the welfare of society and (b) strengthening national economy. Furthermore, IAS shall consider the following unfinished agendas, i.e. (a) rising agricultural population and the declining role of agriculture; (b) rising of urban drift of rural workers may affect the agro/rural industries; (c) if point (b) happened then accelerating growth of the agro-industrial sector will face lack of un-trained personnel; (d) growing the negative impacts of using natural and agricultural resources for industry; and (e) shrinking subsistence farming versus increased cash cropping, coinciding with the depletion of forests, soil and a rise in plant and animal diseases.